Caractérisation Du Contenu Pollinique De L’atmosphère De La Commune d’Abomey-Calavi De 2015 À 2017 - Tchabi F. Lopez; Tossou G. Monique; Zanou R. Adéline; Akoegninou Akpov; Akpagana Koffi (European Scientific Journal, ESJ, 2017)
The Characterization of pollen content of Abomey-Calavi was studied from April 2015 to April 2017, whether two years. A floristic inventory of the species in 7 of the 12 districts of the municipality as well as a collection of pollen grains using the sensor of Hirst were carried out. In total, 104 species in bloom were inventoried each year. Pollen analysis yielded an average of 180 and 182 grains of pollen per cubic meter of air per day from April 2015 to April 2016 and April 2016 to April 2017. They belong to 29 families, 41 genera and 38 species. Among the species inventoried, 47.11% was found in the samples analyzed. The dominant taxa for the two years of study are: Acacia auriculiformis, Poaceae, Combretum indicum and Elaeis guineensis. The daily pollen index of these taxa shows that they are in bloom throughout the year and their main pollination period differs according to the seasons of the year. The correlation is positive between pollen grains and meteorological parameters such as maximum temperature and wind speed but negative between pollen grains, minimum temperature and rainfal.